2017
DOI: 10.31231/osf.io/ptuvd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trauma and the Making of Flexible Minds in the Tibetan Exile Community

Abstract: Mental health in the Tibetan refugee community has been studied extensively, but like most research on political violence, these studies focus almost exclusively on trauma. Studies suggest this exile community seems to be unusually resilient; but from where does this capacity to thrive stem? On the basis of ethnographic research in Dharamsala, India, conducted over 14 months, this article demonstrates how Tibetans conceive of resilience as a learned and active process of making the mind more "spacious" and "fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…By extension, for the Vajrayāna practitioners in our study, the more pervasive discourses around trauma and PTSD in the United States likely influence the extent to which they can adopt a religious framework over a psychological framework when interpreting their experiences. Lewis (2013) also argues that appropriate responses to trauma might also be culturally specific; while Westerners seem to benefit from narrativizing (Brewin et al 2010), 22 such approaches "are in some ways antithetical to Tibetan notions of health coping" (Lewis 2013, p. 317). Keeping this key principle of transcultural psychiatry in mind, the converse might also be equally true: namely, there might be limitations to the application of Tibetan Buddhist frameworks of purification and stances of non-reactivity for the negotiation of trauma among certain populations in the West.…”
Section: Concluding Thoughts On Trauma and Culturementioning
confidence: 99%
See 2 more Smart Citations
“…By extension, for the Vajrayāna practitioners in our study, the more pervasive discourses around trauma and PTSD in the United States likely influence the extent to which they can adopt a religious framework over a psychological framework when interpreting their experiences. Lewis (2013) also argues that appropriate responses to trauma might also be culturally specific; while Westerners seem to benefit from narrativizing (Brewin et al 2010), 22 such approaches "are in some ways antithetical to Tibetan notions of health coping" (Lewis 2013, p. 317). Keeping this key principle of transcultural psychiatry in mind, the converse might also be equally true: namely, there might be limitations to the application of Tibetan Buddhist frameworks of purification and stances of non-reactivity for the negotiation of trauma among certain populations in the West.…”
Section: Concluding Thoughts On Trauma and Culturementioning
confidence: 99%
“…Although some somatic elements of the monks' distress allow for a nice fit between the diagnostic categories of rlung disorder and PTSD, they found that the former does not capture the resurfacing of intrusive traumatic memories. Lewis (2013) has argued that while the label "trauma" is not entirely unknown among Tibetan refugee cultures in India, due to the cultural preference for "letting go" of negative emotions, discourses around trauma "seem to lose, rather than gain momentum through social interactions" (Lewis 2013, p. 316). By extension, for the Vajrayāna practitioners in our study, the more pervasive discourses around trauma and PTSD in the United States likely influence the extent to which they can adopt a religious framework over a psychological framework when interpreting their experiences.…”
Section: Concluding Thoughts On Trauma and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…However, we know little about the person-centered experience of meditation. This article will focus on the stories that American women who use meditation-based contemplative practice as a therapeutic for trauma and their teachers tell about their experiences of “the practice.” The ways that meditation has been used as a treatment for trauma in the US likely diverges from those found in other, more culturally-specific contexts—for example, among Cambodian monks (Nickerson and Hinton 2011) and Tibetan refugees (Lewis 2013). This article will add to this literature to help us better understand how people experience meditation practice as therapeutic in the cultural context of the US.…”
Section: Introductionmentioning
confidence: 99%
“…Because the majority of studies of collective memory in recent years have been studies of political violence, social scientists-influenced by literary theorists-have turned to science and sought to highlight the particular forms of suffering engendered by war with reference to the psychological category of trauma and the psychiatric symptomatology of post-traumatic stress disorder. 6 Leaving aside the problem of universalization and the consequent erasure of context and history implicit in the trauma discourse (Argenti 2007(Argenti , 2016Argenti and Schramm 2010;Broch-Due 2016;Fassin and Rechtman 2009;Hacking 1995;Lewis 2013;Leys 2000;Young 1995), the key point for our current discussion is that trauma is said to break the linearity of psychic time, introducing to it a circularity or short circuit that is the root of the morbidity of the syndrome. The role of the therapist is to interrupt this circularity and to reestablish the linear continuity of psychic time, making of the past a past and of the present an unambiguously monolithic, synchronous moment not haunted by any ghosts.…”
Section: Space Without Places Time Without Duration: Temporalities Omentioning
confidence: 99%